Lactate Dynamics Modulated by mct1 and Glucose Oxidation Shifts in Age-Related Energy Decline in the Corpus Callosum - Rojas-Montecinos, P (Elsevier Inc., 2025)
The global population is aging, as reported by the World Health Organization (WHO). The brain, an energy-dependent organ, experiences a significant decline in energy production as we age. The corpus callosum, a major white matter tract, undergoes changes in energy metabolism during aging that remain poorly understood. This study aimed to investigate axonal energy metabolism in the corpus callosum and the potential role of Monocarboxylate Transporter 1 (MCT1) in age-related metabolic alterations. We analyzed the corpus callosum of young (3–4 months) and aged (18–24 months) mice, focusing on metabolic changes. Metabolomic analysis by gas chromatography-mass spectroscopy (GC-MS) revealed lactate accumulation, reduced glucose levels, and oxidative stress in the aged corpus callosum. Neuronal stimulation experiments using SoNar fluorescent sensor demonstrated a reduced capacity for oxidative energy metabolism in aged axons, evidenced by a lower axonal NADH/NAD + ratio during electrical stimulation. In young axons, oxidative energy metabolism is sustained by glycolysis, lactate production via lactate dehydrogenase (LDH), and lactate transport mediated by MCTs during electrical stimulation. However, these processes are significantly impaired in aged axons. Additionally, glucose oxidation shifted preferentially to the pentose phosphate pathway (PPP) during electrical stimulation, highlighting its role in mitigating oxidative stress in aging. We observed reduced lactate uptake and MCT1 expression in aging. This reduction likely disrupts lactate flux and oxidation, contributing to energy inefficiencies that may promote oxidative stress and axonal deterioration. Our findings emphasize the need for further investigation of the role of MCT1 and lactate metabolism as therapeutic targets to preserve white matter integrity and axonal function in the aging brain. © 2025